2018
DOI: 10.1016/j.cstp.2017.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts between bikes and trucks in urban areas—A survey of Norwegian cyclists

Abstract: Several challenges accompany the current growth of bike and truck volumes in urban areas, with traffic safety being one of the most critical concerns. Bike-truck accidents present a direct measure of the safety; however, these are rare events. Furthermore, accident records are subject to several shortcomings. Thus, safety studies should not rely solely on accident analysis, and conducting the additional methods is advisable (e.g. surveys or conflict analysis). This paper discusses the results of a retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Furthermore, albeit all reviewed conflict studies have recognised the conflicts based on an evasive action, the threshold between evasive and normal action was identified subjectively without any quantification. This potentially contributes to the different conflict rates observed between studies -one study identified two conflicts during 100 h of observation, while the other one identified 71 conflicts in 129 h [30,41].…”
Section: Non-accident Analysismentioning
confidence: 99%
“…Furthermore, albeit all reviewed conflict studies have recognised the conflicts based on an evasive action, the threshold between evasive and normal action was identified subjectively without any quantification. This potentially contributes to the different conflict rates observed between studies -one study identified two conflicts during 100 h of observation, while the other one identified 71 conflicts in 129 h [30,41].…”
Section: Non-accident Analysismentioning
confidence: 99%
“…The first direction of study analysed in a vast array of publications refers to cyclists' interactions with other road users in the context of different infrastructural solutions, most often in relation to potential conflict situations (Silvano et al 2016;Stipancic et al 2016;Apasnore et al 2017;Pokorny et al 2018) and those resulting in accidents (Pokorny et al 2017;Lopez et al 2017). Research also covers the relationship between factors contributing to cyclists' collisions with vehicles and the severity of their injuries (Kim et al 2007).…”
Section: Urban Cycling Safetymentioning
confidence: 99%
“…However, rates vary considerably between summer (12%) and winter (4%) [25]. Relative to other Norwegian cities, the situation for cycling is characterized by reasonable separate infrastructure in a low-density grid outside the city center; however, with a discontinuous inner-city bicycle network [26]. Trips made on foot represent 28% of all journeys in Trondheim, whilst 1% are made by other forms of transport.…”
Section: Case Descriptionmentioning
confidence: 99%